2022
DOI: 10.3389/fnetp.2022.890906
|View full text |Cite
|
Sign up to set email alerts
|

EEG functional brain connectivity strengthens with age during attentional processing to faces in children

Abstract: Studying functional connectivity may generate clues to the maturational changes that occur in children, expressed by the dynamical organization of the functional network assessed by electroencephalographic recordings (EEG). In the present study, we compared the EEG functional connectivity pattern estimated by linear cross-correlations of the electrical brain activity of three groups of children (6, 8, and 10 years of age) while performing odd-ball tasks containing facial stimuli that are chosen considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The average age of the children was 3.92 ± 1.38 (mean ± std), with a range of 2.08–5.92 years. Although the age range of the children was more than 3 years, the EEG correlation pattern was found to be stable at younger ages (less than 6 years) and only started to diverge at 10 years 15 . All children were diagnosed with autism spectrum disorder (ASD) and were referred to the neurology department by pediatricians or child psychiatrists for diagnostic purposes (neurological and metabolic diagnosis according to ICD 10 16 ).…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…The average age of the children was 3.92 ± 1.38 (mean ± std), with a range of 2.08–5.92 years. Although the age range of the children was more than 3 years, the EEG correlation pattern was found to be stable at younger ages (less than 6 years) and only started to diverge at 10 years 15 . All children were diagnosed with autism spectrum disorder (ASD) and were referred to the neurology department by pediatricians or child psychiatrists for diagnostic purposes (neurological and metabolic diagnosis according to ICD 10 16 ).…”
Section: Methodsmentioning
confidence: 80%
“…Our search for early indicators of ASD was based on EEG connectivity in resting-state conditions using clinical data. We selected EEG connectivity for the classification and statistical and ML inferences as the connectivity differences between typically developing children and those with ASD have been identified as one of the most commonly detected using traditional statistics 12 , 15 , 29 36 . Although EEG connectivity delivers promising results, due to a lack of correlations between different methods 12 , studies using different methods have produced somewhat inconsistent results regarding the nature of these differences or even show a lack of associations between EEG connectivity and ASD 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimuli were successfully employed in an emotional recognition study (Benitez-Lopez & Ramos-Loyo, 2022) with a sample of 29 typically developing children with a similar age range (8 to 10.11 years old) and the same race as those of the present study. In addition, the facial database has been used previously in different published studies in adult populations (Llamas-Alonso et al, 2020, 2022, Ramos-Loyo et al, 2022). We used adult stimuli rather than youth to prevent “own-age bias” (Anastasi & Rhodes, 2005; Kuefner et al, 2008; Lamont et al, 2005) as well as the reported poorer performance when children are categorizing other children’s faces by sex.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently found that pairs of brain waves interact through distinct coupling functions, and that physiological states (sleep/wake, sleep stages, rest/exercise, cognitive tasks) and conditions (age maturation) are uniquely characterized by an ensemble of coupling forms among brain waves and by specific network topology necessary to facilitate physiological functions ( Liu K. K. et al, 2015 ; Lin et al, 2020 ; Chen et al, 2022 ; Hu et al, 2022 ; Martinez-Gutierrez et al, 2022 ; Ramos-Loyo et al, 2022 ). Such functional networks among brain waves are expression of synchronization mechanisms integrating different neuronal networks ( Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%